2020
DOI: 10.15388/omee.2020.11.39
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Intelligence and Extra-Role Behavior of Knowledge Employees: Mediating and Moderating Effects

Abstract: This study constructed a model to explore how emotional intelligence (EI) predicts organizational citizenship behavior (OCB) and counterproductive work behavior (CWB) via the mediators of job satisfaction (JS) and work engagement (WE). Furthermore, this study examined whether organizational justice (OJ) and person-organization fit (P-O fit) moderate the effect of EI on OCB and CWB. The model was tested using data from 540 knowledge employees in mainland China. This study found that JS and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Moreover, our results indicate that EI training has a positive effect on training transfer (H4); in particular, EI training has a positive effect on OCB [9,46,49,[125][126][127] and a negative effect on CWB [49,50,127,134,136] 1 month and 3 months after the EI training in both selfand supervisor evaluation samples. This validates the findings of previous studies and confirms their results regarding the direct effect of EI training on training transfer [32,165].…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Moreover, our results indicate that EI training has a positive effect on training transfer (H4); in particular, EI training has a positive effect on OCB [9,46,49,[125][126][127] and a negative effect on CWB [49,50,127,134,136] 1 month and 3 months after the EI training in both selfand supervisor evaluation samples. This validates the findings of previous studies and confirms their results regarding the direct effect of EI training on training transfer [32,165].…”
Section: Discussionmentioning
confidence: 66%
“…Prior studies [9,46,49,[125][126][127] consistently showed the positive effect of EI on OCB. Additionally, Permatasari et al [128] and Goudarzian et al [129] found that EI training can enhance OCB, supported by studies on elementary teachers.…”
Section: Emotional Intelligence Training On Training Transfermentioning
confidence: 89%
See 1 more Smart Citation
“…According to Brannick (2009), the MSCEIT is linked to a person's EI abilities, while the WLEIS is related to personality traits and industry-standard personality tests (NEO). Although a person's knowledge is not connected with their personality, their character is (Yu & Takahashi, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Bununla birlikte Goleman (2006) duygusal zekayı, sosyal zekanın bir formu olarak ortaya atmıştır. Bu nedenle literatürdeki duygusal zekâ ve kişi-örgüt uyumu arasındaki pozitif ilişkiyi ortaya koyan araştırmalar da değerlendirilebilir (Yu ve Takahashi, 2020;Johan ve Yusuf, 2022;Liu, Wang ve Yin, 2023). SMT ve literatürdeki diğer araştırma sonuçlarına dayanarak mevcut araştırmanın ikinci hipotez seti aşağıdaki şekilde geliştirilmiştir: H2: Kişi-örgüt uyumu ile sosyal zekâ arasında pozitif yönlü ilişki vardır.…”
Section: Kişi-örgüt Uyumu Ve Sosyal Zekâ İlişkisiunclassified